А language of personage is in artistic tekst (Herald of Journalism, 2016)
The main structure of investigation in linguistically stylistics is the he ro’s language. Literary text, especially to revue systematically the hero’s language is the main point of investigation such as in literature, linguistics, and artistic semiotics. The style is the main object of linguistics and lit erature. The object of stylistic analyses is not only the word, collocation, sentence and the text, it is also a piece of art.The role of dialogue, monologue and polylogs is very important in analyzing the hero’s language in the text. The article deals with the artistic skills of using the hero’s language, dialogue, monologue and polylogs.
Keywords: stilistika, artistic invent, monologue, dialogue, Language of personage.